ANALISIS PENGARUH KEBIJAKAN PAJAK TERHADAP PERTUMBUHAN EKONOMI NASIONAL DAN PERAN ADMINISTRASI NEGARA DALAM OPTIMALISASI PENERIMAAN PAJAK - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2025)
This study analyses the impact of tax policy on Indonesia's national economic growth and the role of state administration in optimising tax revenue through a comprehensive literature review of academic journals, government reports, and policy documents. The main findings show that tax policies such as adjustments to income tax rates, VAT, and fiscal incentives have a significant positive impact on GDP through the multiplier effect of government spending, while state administration through the SAPT system, risk-based supervision, and digital transformation has succeeded in increasing taxpayer compliance and minimising revenue leakage. The conclusion emphasises the synergy between progressive policy design and efficient administration for sustainable growth, with recommendations for the application of data integration technology and periodic empirical evaluation using VAR models.